[Cutaneous infection by Mycobacterium fortuitum] Infeccion cutanea por Mycobacterium fortuitum - Verónica Rotela; Maria Elena Ibáñez; Beatriz Di Martino Ortiz; Oilda Knopfelmacher Domínguez; Mirtha Rodríguez Masi; Lourdes Bolla Argüello de Lezcano (Our Dermatology Online, 2017)
Mycobacteria are aerobic, non-spore forming, gram positive, acid-fast bacilli, which affect skin, subcutaneous tissue, and other organs and systems. Mycobacterium fortuitum produces cellulitis, abscesses, papules-pustules, nodules and ulcers with serosanguinolent, purulent material, and subcutaneous necrosis. A 61-year-old woman, presents a case of two months of evolution that begins with reddish grain from an insect sting. After immersion in the Mexican Sea, it worsens, increases in quantity, is blistered and has brownish secretion; Physical examination shows erythematous plaque, with punctate orifices with hematic and meliceric crusts; Pustules and satellite papules, on the anterior aspect of the right leg. Histopathology: Suppurative dermal granulomas, centered by acute leukocyte infiltrate, with liquefactive tissue necrosis, surrounded by chronic inflammation with macrophages, plasma cells, lymphocytes, multinucleated giant cells. The first skin culture returns negative; in the second skin culture, fast-growing, non-pigmented atypical mycobacteria. Molecular detection is performed by Polymerase Chain Reaction: Mycobacterium fortuitum. Treatment with Ciprofloxacin 500 mg every 12 hours, with resolution of the table to the eighth month. A case of cutaneous infection by Mycobacterium fortuitum, related to the immersion in the sea and corals, whose diagnostic process has been difficult and was achieved by techniques of advanced molecular biology.